Topical application of tranexamic acid in primary total hip arthroplasty: A systemic review and meta-analysis. (March 2015) - Wang, Chen; Xu, Gui-jun; Han, Zhe; Ma, Jian-xiong; Ma, Xin-long; Jiang, Xuan; Wang, Ying
Abstract: Objective: A systematic review of randomized controlled trials (RCTs) and non-RCTs was performed to evaluate efficacy for the reduction of postoperative blood loss and transfusion requirements of topical use of tranexamic acid in patients undergoing primary total hip arthroplasty. Method: Potential articles were identified from Medline (1966 – September 2014), Embase (1980 – September 2014), Pubmed (1980 – September 2014) and The Cochrane Central Register of Controlled Trials. Other internet databases are also searched to find trials according to the Cochrane Collaboration guidelines. Moreover, gray literatures are also selected from the reference list of the included studies. High quality randomized controlled trials (RCTs) and non-RCTs were selected. The software RevMan 5.1 was used for the mate-analysis. Results: Four RCTs and four non-RCT meet the inclusion criteria. There were significant differences in hemoglobin, total blood loss, transfusion requirements and postoperative drainage volume between TXA groups and control groups. There were no significant differences in length of stay, incidence of wound infection, deep vein thrombosis (DVT) and pulmonary embolism (PE) between treatment and control groups. Conclusions: Present meta-analysis indicates that the antifibrinolytic agent, also known as tranexamic acid, could reduce hemoglobin decline, volume of drainage, total blood loss and transfusion requirements after THA, and is not related to adverse reactions or complications such as wound infection, DVT and PE. Highlights: We conducted a meta-analysis to evaluate efficiency of topical use of tranexamic acid in patients undergoing primary THA. Only high quality studies were selected. Topical application of tranexamic acid for patients undergoing primary total hip arthroplasty is effective and safe.